2021
DOI: 10.1108/wje-05-2021-0260
|View full text |Cite
|
Sign up to set email alerts
|

Fluid elastic instability and vortex induced vibration parameters in finned tube arrays with P/D ratio 1.79

Abstract: Purpose This paper aims to analyze the effect of fin geometry on mechanisms of flow induced vibration. Finned tube arrays are used in a heat exchanger to increase its efficiency. Therefore, it is necessary to investigate the effect of geometric parameters of the fin fluid elastic instability and vortex shedding. In this paper, the effect of fin height, fin density and tube pitch ratio for parallel triangular tube array on fluid elastic instability and vortex shedding is analyzed. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For aluminum and steel tubes, this ratio is approximately same. The modal parameters obtained by free vibration testing of steel tubes of the same geometry as that of aluminum tubes used for experimentation are compared with the results obtained numerically, showing good agreement (Yadav and Mohanty, 2021c, d). The natural frequency obtained in still water for the plain tube and tube with 3 mm fin height is identical because the mass ratio is approximately same.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…For aluminum and steel tubes, this ratio is approximately same. The modal parameters obtained by free vibration testing of steel tubes of the same geometry as that of aluminum tubes used for experimentation are compared with the results obtained numerically, showing good agreement (Yadav and Mohanty, 2021c, d). The natural frequency obtained in still water for the plain tube and tube with 3 mm fin height is identical because the mass ratio is approximately same.…”
Section: Resultsmentioning
confidence: 90%
“…, 2018; Mitra et al. , 2009; Yadav and Mohanty, 2021c, d). Weaver and Yeung (1984) investigated the effect of tube mass on the instability threshold for various tube array patterns and concluded that fluid elastic instability is mass ratio independent.…”
Section: Introductionmentioning
confidence: 99%
“…The water cross flow experiments with finned tube arrays are conducted, and research data are published by a few researchers in the recent past. Yadav and Mohanty (2021a) have conducted the experiments to investigate the effect of fin density, fin height and pitch ratio on the fluid elastic instability and vortex shedding behavior of parallel triangular tube arrays made of copper material. The effect of fin geometry and pitch ratio on the fluid elastic instability of parallel triangular finned tube arrays of steel material was studied by Yadav and Mohanty (2021b) by conducting experiments in water cross flow.…”
Section: Finned Tubes In Water Cross Flowmentioning
confidence: 99%
“…The effect of fin geometry and pitch ratio on the fluid elastic instability of parallel triangular finned tube arrays of steel material was studied by Yadav and Mohanty (2021b) by conducting experiments in water cross flow. The comparison of the results of the experiments conducted by Yadav and Mohanty (2021a, b) indicate that instability threshold is delayed for copper tube arrays compared to steel tube arrays. Desai and Pavitarn (2016, 2017) tested parallel triangular finned tube arrays in water cross flow to study their fluid elastic instability and vortex shedding behavior.…”
Section: Introductionmentioning
confidence: 99%